Bamboo Resource Utilization, Household Dependency and Livelihood Dynamics in Karbi-Anglong District, Assam - Borah, Sidharth Narayan; Sarma, K.; Sarma, A.k. (International Journal of Aquatic Research and Environmental Studies, 2026)
Bamboo is one of the most indispensable biological resources in Northeast India, supporting a diverse range of applications, sustainable livelihoods, traditional practices, and daily household requirements. The present study assessed the utilization, household dependency, and livelihood dynamics associated with bamboo resources in Karbi-Anglong district, Assam. A stratified mixed multi-stage sampling approach was adopted, wherein 2 forest ranges, 11 forested regions and 16 villages were covered across Karbi-Anglong East and West. A total of 450 respondents were surveyed for primary data collection, using Participatory Rural Appraisal (PRA) tools, such as focus-group discussions, key-informant interviews, semi-structured questionnaire surveys, and field observations. The findings revealed that bamboo was cultivated by all households within their homestead gardens. The area under bamboo in the homestead gardens of Karbi Anglong East was observed to be higher than that of Karbi Anglong West. Five major bamboo species were documented, of which Bambusa tulda and Dendrocalamus hamiltonii were identified as the most socio-economically important species. The former was prioritized for construction purposes, while the latter was preferred by the households for handicrafts and bamboo shoot consumption. Bamboo utilization was predominantly household-oriented, with 93% of households cultivating bamboo to meet their daily subsistence requirements, highlighting limited commercialisation. Forest dependency was relatively low, although specific species continued to be traditionally procured from forests. The bamboo market structure was largely informal, fragmented, small-scale, characterised by weak market linkages and irregular demand. The study highlights the crucial role of bamboo in sustaining rural livelihoods and focus on strengthening resource management, market linkages, value addition, and capacity-building initiatives for overall development of the bamboo sector in the study area.
Keywords: Livelihood dynamics, Homestead gardens, Participatory Rural Appraisal, Subsistence, Karbi Anglong, Household dependency